2013
DOI: 10.1111/cga.12011
|View full text |Cite
|
Sign up to set email alerts
|

Wnt11 expression in rat dental pulp and promotional effects of Wnt signaling on odontoblast differentiation

Abstract: Congenital anomalies of wingless-type mouse mammary tumor virus (MMTV) integration site family (Wnt) are frequently accompanied with tooth and dentin abnormality. The aim of this study was to investigate the effects of Wnt signaling on odontoblast differentiation of mouse dental papilla cells (MDPs). Mouse dental papilla cells were cultured in α-modified minimum essential medium containing 10% fetal bovine serum and antibiotics. Odontoblast differentiation was induced by bone morphogenic protein 2 (BMP2), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Recent reports demonstrate that IL-1β-induced MMP-3 is associated with the secreted glycoprotein Wnt signaling pathway (15). We have also demonstrated that IL-1β-induced MMP-3-regulated proliferation of mouse ESCderived odontoblastic cells is mediated by the Wnt5a-and 5b-signaling pathways (16).…”
Section: Introductionsupporting
confidence: 53%
“…Recent reports demonstrate that IL-1β-induced MMP-3 is associated with the secreted glycoprotein Wnt signaling pathway (15). We have also demonstrated that IL-1β-induced MMP-3-regulated proliferation of mouse ESCderived odontoblastic cells is mediated by the Wnt5a-and 5b-signaling pathways (16).…”
Section: Introductionsupporting
confidence: 53%
“…The other growth factors involved in odontoblast differentiation include epidermal growth factor (Liang et al ; Liang et al ), FGF2 (Nakao et al ; Shimabukuro et al ; Morito et al ; Shimabukuro et al ), growth differentiation factor 11 (Nakashima et al ; Nakashima et al ), platelet‐derived growth factor (PDGF) (Yokose et al ), hepatocyte growth factor (Li et al ), and insulin‐like growth factors (IGF) (Onishi et al ). Odontoblast differentiation is modulated by various molecules, including twist (Galler et al ), Nuclear factor I‐C (Lee et al ), Notch (Zhang et al ; Sun et al ), Wnt (Scheller et al ; Koizumi et al ), Runx2, Sp7 (Chen et al ), Runx3 (Zheng et al ), and DLX3 (Choi et al ). However, the specific factor(s) or gene(s), including master genes, required for commitment to odontoblast differentiation remain unclear.…”
Section: Morphology and Development Of Odontoblastsmentioning
confidence: 99%
“…The mRNA and protein levels of both factors were increased by Poly(P). Bone-associated cells also express other Wnt proteins such as Wnt3a, Wnt6, Wnt10a, and Wnt11 (41)(42)(43). To assess whether the induction of Wnt5a and Wnt5b by Poly(P) is a specific response in DPFCs, we evaluated the expression of these other Wnt proteins following treatment with the same concentrations of Poly(P).…”
Section: Poly(p)-induction Of Wnt5a and Wnt5b Mrna And Protein Expresmentioning
confidence: 99%